2010
DOI: 10.1007/bf03245888
|View full text |Cite
|
Sign up to set email alerts
|

A novel and efficient one-pot method to Biginelli-like scaffolds

Abstract: A novel and efficient one-pot method for the preparation of fused ring 3,4-dihydropyrimidin-2(1H)-ones and thiones from cyclocondensation of aldehydes, cyclic ketones and urea or thiourea using a catalytic amount of cupric chloride under mild conditions reaction is described. This new method has the advantage to give high yields, to be completed in short reaction times and simple product isolation procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…Both BF 3 ∙OEt 2 and BBr 3 caused no obvious enhancement of the reaction yield ( Table 1 , entries 7 and 8). As TMS-X-type (X = Cl, I, OTf) compounds were proved to be efficient reagents which could significantly promote Biginelli-like reactions [ 44 , 45 , 56 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ], we then explored the effects of this kind of additive. We found that TMSOTf, TMSCl, TMSBr and TMSI could improve the yield to different degrees ( Table 1 , entries 9–12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both BF 3 ∙OEt 2 and BBr 3 caused no obvious enhancement of the reaction yield ( Table 1 , entries 7 and 8). As TMS-X-type (X = Cl, I, OTf) compounds were proved to be efficient reagents which could significantly promote Biginelli-like reactions [ 44 , 45 , 56 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ], we then explored the effects of this kind of additive. We found that TMSOTf, TMSCl, TMSBr and TMSI could improve the yield to different degrees ( Table 1 , entries 9–12).…”
Section: Resultsmentioning
confidence: 99%
“…However, this method suffered from low yields and the usage of strong acids. Consequently, improved procedures, including the employment of Lewis acid catalysts [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], bases [ 57 , 58 ], ionic liquids [ 59 , 60 , 61 , 62 ], ultrasound irradiation [ 63 ], and nanocomposites [ 64 , 65 , 66 ] have been developed. Despite the remarkable achievements made, however, many of these methods still suffer from major or minor drawbacks, such as long reaction time, harsh reaction conditions, low yields, the stoichiometric requirements of the metal catalysts and the involvement of expensive or toxic reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Далее полученный полупродукт вступает в конденсацию с 3,4-дигидронафта-лин-1(2Н)-оном. Последующая N-циклизация (14) и дегидратация (11, 12) ведут к образованию целевых бензохиназолинонов (7)(8)(9)(10).…”
Section: -10 2-4unclassified
“…При этом, согласно экспериментальным дын-ным и классическому механизму, в качестве продуктов выделены 3,4,5,6-тетрагидро-4-(4-R-фенил)бензо[h]хина золин-2(1H)-(ти)оны с использованием ионной жидкости хлорид сульфопиридиния [7] и 1-метил-3-(4-сульфобутил)имидазол-4-метилбензолсульфоната [8]. При термическом режиме проведения превращения с нитробензаль-дегидом и мочевиной в качестве катализаторов использовались: HCl, CuCl, CuCl 2 , I 2 [9]. И на одном примере в условиях микроволновой активации реагентов с участием тиомочевины и катализатора HCl удается также получить 3,4,5,6-тетрагидро-4-(4-R-фенил)бензо[h] хиназолин-2(1H)-тионы [10].…”
unclassified
“…In continuation of our investigations in heterogeneous catalysis [36,[42][43][44][45][46] and the preparation of heterocyclic products [47][48][49][50][51], we describe herein the application of MCR for the preparation of 4H-pyran compounds (1a-t and 2a) using an eco-friendly diethylenetriamine-functionalized reduced GO (rGO-DETA) catalyst as a solid base material in water media under mild conditions (Scheme 1). The reaction of 4Hpyran compounds with cyclohexanone gave high yields of the corresponding pyran-like tacrine derivatives 3f and 3h.…”
Section: Introductionmentioning
confidence: 99%